Formulasi dan Uji Efektivitas Repellent Spray Gel Minyak Atsiri Daun Kayu Manis (Cinnamomum burmannii) Sebagai Penolak Nyamuk - Syarli, Silviera; Elisma, Elisma; Lestari, Uce; Rahmadona, Tasha; Herawati, Ariana; Najwa, Shinta; Delfina, Rahmanda Ayu (Jurnal Pelayanan Kefarmasian dan Sains, 2025)
Background:  Mosquitoes are insects that have the potential to be vectors or carriers of diseases to humans, including Dengue Fever (DBD), chikungunya, filariasis, and Japanese Encephalitis. Cinnamon leaves (Cinnamomum burmannii) are known to have eugenol compounds that can act as insecticides derived from natural ingredients. Objective: To determine the physical properties and effectiveness of cinnamon leaf essential oil against mosquitoes in the form of spray gel preparations. Methods:  The process of making spray gel preparations from Cinnamon Leaf Essential Oil uses variations in essential oil concentrations of 5%, 10%, and 15%. The base used as a gelling agent is Carbopol 940. Evaluation of the physical properties of the preparation includes organoleptic tests, homogeneity tests, pH tests, viscosity tests, spreadability tests, and adhesion tests. Result: The results of the study showed that differences in essential oil concentrations can affect the physical properties and effectiveness of spray gel preparations as mosquito repellents. Of the three formulas, F1 5%, F2 10%, and F3 15%, the best preparation is F2 with a concentration of Cinnamon Leaf Essential Oil (Cinnamomum burmannii) of 10% v/v. Conclusion:  The formula with the best results of physical properties and effectiveness were F2 with a concentration of 10%, which had an average protection power value of 82.4% with physical properties that met the requirements of a spray gel preparation.